PENERAPAN PROFIL PELAJAR PANCASILA DIMENSI BERNALAR KRITIS PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Ifliadi, Ilham; Nazurty; Sukendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the implementation of the Pancasila Student Profile with a critical reasoning dimension in IPAS (Integrated Science) learning, and the supporting factors as well as the inhibiting factors of implementing the Pancasila Student Profile with a critical reasoning dimension in IPAS learning at SDN 19/IV Kota Jambi. This research was conducted at SDN 19/IV Kota Jambi. The research approach is qualitative with a descriptive study type. The data sources for this research include 1 school principal, 1 fourth-grade teacher, and 2 fourth-grade students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques used reduction, data display, and verification. The results of this study indicate that the implementation of the Pancasila Student Profile with a Critical Reasoning Dimension in IPAS Learning for the fourth grade at SDN 19/IV Kota Jambi involves stages: 1) Planning, which is done by holding annual meetings about the programs to be implemented, teachers conducting diagnostic assessments to see the abilities of the students and mapping them, determining topics, and preparing teaching tools such as compiling LKPD teaching modules and assessment instruments. 2) Implementation, which focuses on the critical reasoning dimension as the dimension developed for Strengthening the Pancasila Student Profile. 3) Evaluation, which consists of formative and summative evaluations. The supporting factors for the implementation of the Pancasila Student Profile with a critical reasoning dimension are support from various parties such as the school principal, teachers, school committee, parents, students, and education observers. Meanwhile, the inhibiting factors include 1) teachers who are confused about working on modules and are still learning, 2) the time it takes to work on modules, 3) knowledge and understanding of the value of justice, 4) awareness of the surrounding environment.